PMO-172 Direct non-invasive serum markers of liver fibrosis predict fibrosis evolution in chronic hepatitis C but are increased by interferon-based therapy. (28th May 2012) - Tanwar, S; Trembling, P M; Ellis, E; Parkes, J; Herold, C; Schuppan, D; Rosenberg, W M C
Abstract : Introduction: Liver biopsy remains the reference standard for the detection of liver fibrosis. While non-invasive markers of liver fibrosis have been validated in chronic hepatitis C, their performance during interferon-based therapy is not established. Methods: 70 previous non-responders to interferon based therapy for chronic hepatitis C (40 male, age range 24–67, mean 48.7) were recruited from five centres. Patients were randomised to receive pegylated interferon with or without silymarin for 24 months as an exploratory antifibrotic therapy. All patients underwent a liver biopsy and ELF tests (HA, P3NP, TIMP-1) prior to, and after treatment (month 0 and 24). Changes in histological fibrosis stages before and after therapy (0 to 24 months) were compared with changes in marker scores before, during and after therapy (0 to 24 months). Results: Mean ELF score prior to therapy was 9.32 (SD 1.10), during therapy 9.91 (SD1.18) and after therapy 9.53 (SD 1.27). ELF scores were significantly higher during therapy than when compared to both before therapy (p<0.00001) and after therapy (p=0.0002) but levels before therapy were not significantly different from post therapy. Elevated scores on therapy were attributable to an increase in mean HA (p<0.0002) and P3NP (p<0.01) levels on therapy, whereas a significant change in mean TIMP-1 during therapy was not seen. These elevations were seen in all patients regardless of changes in histological fibrosis after therapy (n=20 decrease, n=25 no change, n=35 increase in Ishak stage). However, individual changes in TIMP1 (r=0.239, p=0.04) and changes in ELF (r=0.315, p=0.004) from pre- to post-therapy levels were found to correlate with the change of Ishak fibrosis stage before and during treatment. Conclusion: During interferon-based therapy, levels of HA and P3NP and the ELF score rise globally and subsequently fall to values similar to those seen prior to therapy regardless of fibrosis evolution, while TIMP1 levels remained unaffected. However, ELF scores pre and post therapy did accurately reflect changes in histology. This suggests that ELF scores and non-invasive panels incorporating HA and P3NP should be interpreted with caution during interferon-based therapy. Competing interests: None declared.